CXCR4-enriched T regulatory cells preferentially home to bone marrow and resolve inflammation - Meixian Huang; Zeng Ke; Mi-Ae Lyu; Lucia Masarova; Tara Sadeghi; Christopher R. Flowers; Simrit Parmar (iScience, 2024)
Summary: CXCR4 cell surface expression is critical for the homing of T regulatory (Treg) cells to the bone marrow (BM). We hypothesize that CXCR4 enrichment on Tregs cell surface may abbreviate their transit time to reach BM. Umbilical cord-blood CD25+ Tregs underwent CXCR4 dual enrichment and ex vivo expansion using the CRANE process to generate CXCR4-enriched Tregs (TregCXCR4) cells, which showed a faster migration across the Transwell membrane toward CXCL12/stromal cell-derived factor 1α (SDF1α) at 15, 30, and 60 min, when compared to unmanipulated Tregcontrol cells (p < 0.0001). TregCXCR4 exhibited preferential homing to BM in vivo at 12 and 24 h. Metacluster analysis of BM showed a decrease in CD8+ and an increase in CD39 and CD73 and CXCR5 when compared to Tregcontrol. TregCXCR4 decreased plasma TGF-β1/β2 and IFN-γ levels. When compared to control, TregCXCR4 cells decreased in CD8+ T cell, IFN-γ, and TNF-α expression in BM. We conclude that TregCXCR4 show enhanced migration toward CXCL12/SDF1α and a preferential homing to BM resulting in resolution of inflammation.